2002
DOI: 10.1055/s-2002-20060
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination of Medicinal Plants - A Review*

Abstract: Medicinal plants may be associated with a broad variety of microbial contaminants, which are represented by bacteria, fungi and viruses. Inevitably, this microbiological background depends on several environmental factors and exerts an important impact on the overall quality of herbal products and preparations. Risk assessment of the microbial load of medicinal plants has therefore become an important subject in the establishment of modern Hazard Analysis and Critical Control Point (HACCP) schemes. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 18 publications
0
90
0
16
Order By: Relevance
“…A contaminação por esses microrganismos pode acarretar deterioração do material por ser fonte de enzimas e de patógenos, podendo levar ao desenvolvimento de doenças. São produtos de alto risco, sendo necessário definir medidas adequadas de controle higiênico-sanitário para garantir a qualidade e segurança deste tipo de produto desde a coleta, armazenamento e manipulação até o produto final (Kneifel et al, 2002).…”
Section: Procedimentos De Controle Microbiológicounclassified
“…A contaminação por esses microrganismos pode acarretar deterioração do material por ser fonte de enzimas e de patógenos, podendo levar ao desenvolvimento de doenças. São produtos de alto risco, sendo necessário definir medidas adequadas de controle higiênico-sanitário para garantir a qualidade e segurança deste tipo de produto desde a coleta, armazenamento e manipulação até o produto final (Kneifel et al, 2002).…”
Section: Procedimentos De Controle Microbiológicounclassified
“…Upon re-hydration, these microorganisms use the proteins and carbohydrates of the plant material to grow, and have to detoxify some of the plants' metabolites to survive, as several metabolites have some sort of generic antimicrobial activity, as described for example for iridoid glycosides (IGs) present in Plantago lanceolata -via protein crosslinking activity (Senatore et al, 2007). Many publications are available in the literature on the microbiological community of medicinal plant raw materials (for a review, see (Kneifel et al, 2002)). …”
Section: Introductionmentioning
confidence: 99%
“…Apart from causing diseases, these micro-organisms could lead to rapid deterioration of the products thus invariably affecting their safety and efficacy. Previous studies on herbal products have shown wide variety of microbial contaminants [32,33]. Microbial contamination of herbs and/or products can result from improper handling during production and packaging.…”
Section: Citationmentioning
confidence: 99%